Shakespeare's Bombastic Blanks. (30th June 2021) - Stagg, Robert
Abstract: This article takes seriously Robert Greene and/or Henry Chettle's 1592 claim that there is something bombastic about Shakespeare's blank verse by focusing on its so-called 'metrical end-stop'. After sketching a survey of the metrical end-stop in early blank verse, it considers the resources with which Shakespeare sought to shift his verse style away from that particular prosodic feature. The article concludes by thinking about the late blank verse of The Winter's Tale as a metrical rejoinder to Greene, whose Pandosto it versifies—though it is a rejoinder that ultimately proves equivocal.